Effect of Platelet-Rich Plasma on the Peri-implant Bone Response: - Fontana, Sebastián (2004)
Platelet-rich plasma (PRP) is used as a source of growth factors to stimulate and accelerate bone formation and soft tissue healing. The use of PRP in bone regeneration, both around dental implants and in periodontic treatments, has become particularly appealing. The aim of this study was to evaluate the effect of PRP in an experimental model of osteogenesis around laminar implants. Fifteen male Wistar rats, weighing 90 +/- 10 g, were used in this study. One milliliter of blood was obtained from each animal by intracardiac puncture and transferred into Eppendorf tubes containing 10% sodium citrate. The tubes were centrifuged at 1500 rpm for 15 minutes and PRP was prepared. The laminar test was used to evaluate the bone peri-implant response. PRP and a titanium laminar implant were introduced into the right tibia (Ti/PRP group), whereas the left tibia (control) received only a laminar implant (Ti group). Thirty days postimplantation, the tibiae were resected, radiographed, and processed for embedding in acrylic resin. Ground sections (50 microm) were stained with toluidine blue. The peri-implant bone volume was evaluated histomorphometrically. Statistical analysis of the data was performed. The amount of newly formed bone in the Ti/PRP group (30 +/- 7 cm) was significantly greater than in the Ti group (16 +/- 3 cm). A greater volume of peri-implant bone was observed when PRP was used in the laminar implant test model.